EVALUASI IPAL RUMAH POTONG HEWAN DALAM RANGKA SENTRALISASI PEMOTONGAN HEWAN DI KOTA PONTIANAK - Joni Hermana (Purifikasi, 2003)
The purpose of this research was to evaluate the unit of slaughterhouse treatment plant and find the basic problems, which caused it couldn’t work as properly. Then designed a strategy to attract the operator of illegal slaughterhouses to do the activity at the legal slaughterhouse. The result showed that there were several strategies that could be implemented on this case and divided into two major strategies, which were technical strategy and the non technical strategy with depend on its urgency which were long term strategy, middle term strategy and short term strategy.